2018
DOI: 10.18632/oncotarget.25809
|View full text |Cite
|
Sign up to set email alerts
|

A short-chain fatty acid, propionate, enhances the cytotoxic effect of cisplatin by modulating GPR41 signaling pathways in HepG2 cells

Abstract: Short-chain fatty acids (SCFAs) such as acetate, propionate, and butyrate are generated by microbial fermentation of indigestible fiber by gut flora. SCFAs are ligands of two orphan G protein-coupled receptors, GPR41 and GPR43, that modulate cell proliferation and induce apoptosis. However, it is unclear if SCFAs enhance the effects of chemotherapy in a GPR41- or GPR43-dependent manner. The aim of this study was to investigate whether SCFAs, and particularly propionate, activate GPR41 or GPR43, and thereby enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…We previously showed that propionate, a physiological GPR41/FFA3 agonist, enhanced the cytotoxicity of cisplatin in HCC cells, and that cisplatin and propionate in combination significantly suppressed growth of HepG2 xenografts in comparison with cisplatin alone. 11 Similarly, AR420626, a selective GPR41/FFA3 agonist, significantly suppressed growth of HepG2 xenografts (p < 0.01) ( Figure 1). There was no significant difference in daily food intake or body weight changes between the control and AR groups (Supplementary Figure S1), and no deaths in either group.…”
Section: Ar420626 Inhibits Growth Of Hepg2 Xenograftsmentioning
confidence: 84%
“…We previously showed that propionate, a physiological GPR41/FFA3 agonist, enhanced the cytotoxicity of cisplatin in HCC cells, and that cisplatin and propionate in combination significantly suppressed growth of HepG2 xenografts in comparison with cisplatin alone. 11 Similarly, AR420626, a selective GPR41/FFA3 agonist, significantly suppressed growth of HepG2 xenografts (p < 0.01) ( Figure 1). There was no significant difference in daily food intake or body weight changes between the control and AR groups (Supplementary Figure S1), and no deaths in either group.…”
Section: Ar420626 Inhibits Growth Of Hepg2 Xenograftsmentioning
confidence: 84%
“…The large concentrate intake could start-up enterocytes gluconeogenesis process, activated the tight junction signaling pathway, then regulated downstream related cell apoptosis pathways, which decreased the tight junction proteins expressions, such as Occluding, Claudin and Zo-1. Meanwhile, the proliferation of Regulatory T Cells to secrete many anti-inflammatory cytokines (IL-6, TNF-α, CCL5), promoted the inflammatory response pathway (MAPK) related genes expression [24,25] . GPR41 was detected in the current study, and presented significantly up-regulated in concentrate-fed group, it showed that long-term high dietary concentrate feeding changed the normal jejunal metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle arrest and DNA damage can trigger autophagy in response to cytoplasmic signals [152]. Lipids such as short-chain fatty acids (mostly propionate and butyrate) could induce autophagy [153] and/or apoptosis [154], as substantiated in colon cancer cells.…”
Section: Interrelation Between the Five Identified Processesmentioning
confidence: 99%